2023
DOI: 10.1590/1678-9865202336e220106
|View full text |Cite
|
Sign up to set email alerts
|

Food practices and nutritional status of university students who use the University Restaurant

Gabriela Ferreira dos Anjos Araujo,
Alessandra da Silva Pereira,
Cláudia Roberta Bocca Santos
et al.

Abstract: Objective To evaluate the food practices and nutritional status of students who use the University Restaurant at a public university. Methods This is a cross-sectional study carried out with 958 university students. Data related to regular eating practices (≥5 times/week), routine food consumption and nutritional status were collected. The association between University Restaurant attendance and dietary practices and body mass index was reviewed by bivariate logistic regression model and multiple regression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Meanwhile, [7], reported 35% and 51% of the respondents consume vegetables and fruits respectively at least three times a week. [13], reported that 44.9% consume vegetables at least three times a week and 41.3% consume fruits at least three times a week. However, this study showed that pepper, tomatoes and onions were the most consumed vegetables on a daily basis by the students with 26.8% and 26.4%, 27.2% respectively, while Okra and Orange were the least (0.9%) consumed fruits and vegetables consumed daily.…”
Section: E Lifestyle Practices Of the Respondentsmentioning
confidence: 99%
“…Meanwhile, [7], reported 35% and 51% of the respondents consume vegetables and fruits respectively at least three times a week. [13], reported that 44.9% consume vegetables at least three times a week and 41.3% consume fruits at least three times a week. However, this study showed that pepper, tomatoes and onions were the most consumed vegetables on a daily basis by the students with 26.8% and 26.4%, 27.2% respectively, while Okra and Orange were the least (0.9%) consumed fruits and vegetables consumed daily.…”
Section: E Lifestyle Practices Of the Respondentsmentioning
confidence: 99%